IMPLEMENTASI PERANCANGAN BANGUNAN MENGGUNAKAN APLIKASI GOOGLE SKETCHUP 8 - Mesterjon, Mesterjon (Jurnal Media Infotama, 2012)
Implemetation Of Building Design Aplications Using Google Sketchup 8 (2012). Informatics Engineering Program Computer Science Faculty of the University of Bengkulu Dehasen, June 2012.This study aims to design building using Google SketchUp application, in order to facilitate the CV. Bumi Permata Sentosa in the design of building design and implement the marketing process.Data collection methods used the making this thesis are the observation, literature, and interviewa. From the results of research conducted it can be conclouded that the design of the building design can be more efficient and effective if implemented into design of three demensional, so the end result can be persentations.